Faktor-faktor yang Mempengaruhi Kelengkapan Pengungkapan Laporan Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Jakarta - Binsar H. Simanjuntak; Lusy Widiastuti (The Indonesian Journal of Accounting Research, 2013)
The aim of this research is to find the factors that influence financial statement disclosure comprehensiveness. This research used 34 manufacturing companies listed at Jakarta Stock Exchange in the period of 2002. The tools analysis  used in this research are multiple-linier regression analysis and t-test.The independent variables i.e. leverage, liquidity, profitability,  the portion of stock owned by public investors and company age are predicted to influence financial statement disclosure comprehensiveness. The results of this research show that leverage variable which proxied by debt to equity ratio, profitability, the portion of stock owned by public investors are significantly and positively associated with financial statement disclosure comprehensiveness.Hopely, in the next research, other variables should be tested. This is important  because there are a lot of other variables influencing financial statement disclosure comprehensiveness, such as firm size,securities issuance in the subsequent year and firm status.